International journal of aerospace engineering (Hindawi Pub. Corp., 2008)
"[The] International Journal of Aerospace Engineering aims to serve the international aerospace engineering community through dissemination of scientific knowledge on practical engineering and design methodologies pertaining to aircraft and space vehicles. Original unpublished manuscripts are solicited in all areas of aerospace engineering, including but not limited to mechanics of materials and structures, aerodynamics and fluid mechanics, dynamics and control, aeroacoustics, aeroelasticity, propulsion and combustion, avionics and systems, flight simulation and mechanics, and unmanned air vehicles (UAVs)"--Journal home page (Hindawi Web site, viewed Jan. 29, 2008).